2010
DOI: 10.1128/aem.02085-09
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Dehydrogenase Required for Lactose Metabolism inCaulobacter crescentus

Abstract: Caulobacter crescentus, which thrives in freshwater environments with low nutrient levels, serves as a model system for studying bacterial cell cycle regulation and organelle development. We examined its ability to utilize lactose (i) to gain insight into the metabolic capacities of oligotrophic bacteria and (ii) to obtain an additional genetic tool for studying this model organism, aiming to eliminate the basal enzymatic activity that hydrolyzes the chromogenic substrate 5-bromo-4-chloro-3-indolyl-␤-D-galacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 61 publications
1
24
1
Order By: Relevance
“…Whether these two proteins act together or sequentially on the substrates to form the 3-ketodisaccharide is also unsolved. As Arellano et al (40) have suggested for C. crescentus, thuA and -B could code for two subunits of this enzyme. A limited and delayed growth was observed in leucrose-grown cultures of At7023 complemented with thuA of S. meliloti (Fig.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Whether these two proteins act together or sequentially on the substrates to form the 3-ketodisaccharide is also unsolved. As Arellano et al (40) have suggested for C. crescentus, thuA and -B could code for two subunits of this enzyme. A limited and delayed growth was observed in leucrose-grown cultures of At7023 complemented with thuA of S. meliloti (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…We have also been consistently unsuccessful in our attempts to detect other known intermediates of trehalose breakdown, such as glucose-6-phosphate, in reaction mixtures containing trehalose and induced S. meliloti cells or cell extracts, through thin-layer chromatography (TLC), HPLC, or HPLC-MS (results not presented). Previous studies with the related alphaproteobacte-rium A. tumefaciens suggested that disaccharide utilization pathways involving dehydrogenase activity may lead to the formation of 3-ketosugars (33,40,41). A. tumefaciens has also been shown to possess the unique ability not only to oxidize sucrose into its 3-keto derivative but also to secrete this compound into the culture medium (41).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To accomplish this, a plasmid‐borne translational P urcA ‐ lacZ fusion (NJH123; Hillson et al ., ) was amplified with primers P urcA _UR_F and P urcA _UR_R (Table S12), and a fragment containing the 517‐bp region downstream of the urcA stop codon was amplified from the chromosome using P urcA _DR_F and P urcA _DR_R. Both fragments were cloned into the HindIII and BamHI‐digested pNPTS138 using In‐Fusion cloning and integrated into the chromosome of a lacA mutant (Arellano et al ., ) or NA1000 using the double‐crossover allele replacement as described above, yielding strains DMP89 and DMP90, respectively (Table S11). For the transposon screen, DMP89 was electroporated with VMCS2:: Tn5Pvan (Christen et al ., ) and plated onto PYE agar plates containing 40 μg ml −1 Xgal, 25 μg ml −1 kanamycin and 0 or 40 μM ZnSO 4 , yielding a total of ∼60,000 colonies.…”
Section: Methodsmentioning
confidence: 99%
“…50 51 One of the most well studied constituents of the human microbiota is the Gram-negative gut 52 anaerobe Bacteroides thetaiotaomicron, which is prevalent in a substantial fraction of the 53 world's population 8 . Pioneering work on the human microbiota revealed the broad range of 54 complex polysaccharides and simple carbohydrates that B. thetaiotaomicron can degrade and 55 ferment in the gut [9][10][11] . Subsequently, analyses enabled by the full genome sequence of B.…”
Section: Introduction 38mentioning
confidence: 99%